1986
DOI: 10.1002/ana.410200205
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid plaques in Creutzfeldt‐Jakob disease stain with prion protein antibodies

Abstract: Amyloid plaques are found in the brains of some patients with Creutzfeldt-Jakob disease (CJD) and all patients with a related transmissible disorder, Gerstmann-Sträussler syndrome (GSS). In scrapie, a prion disease of animals, amyloid plaques have been shown to be composed of prion proteins (PrP), which form filaments of relatively uniform diameter. We report here that antisera raised against hamster scrapie PrP specifically stain amyloid plaques in the brains of both humans and rodents with CJD as well as a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…PrPsc has been generally distinguished from cellular PrP (PrPC) by its relative protease resistance, its insolubility in nondenaturing detergents, its enhanced antigenicity after denaturation, and its posttranslational biogenesis; spectroscopic studies show that the two proteins differ in their conformations (23). When amyloid plaques are present in these patients, the plaques stain with anti-PrP antibodies (24)(25)(26).…”
mentioning
confidence: 99%
“…PrPsc has been generally distinguished from cellular PrP (PrPC) by its relative protease resistance, its insolubility in nondenaturing detergents, its enhanced antigenicity after denaturation, and its posttranslational biogenesis; spectroscopic studies show that the two proteins differ in their conformations (23). When amyloid plaques are present in these patients, the plaques stain with anti-PrP antibodies (24)(25)(26).…”
mentioning
confidence: 99%
“…PrP 27-30 was subsequently shown to be derived by limited proteolysis from a larger protein designated PrPSc, which is encoded by a chromosomal gene and not by a putative nucleic acid within the prion (2,44). Although many biochemical (6,44,51), genetic (2,7,65), and pathological (4,5,36,52) results argue persuasively that PrPsc is a component of the infectious scrapie particle, only recently have immunoaffinity chromatography and neutralization data been obtained that establish that this is indeed the case (22a). Dispersion of prions into detergent-lipid-protein complexes permitted purification of scrapie infectivity by a PrP monoclonal antibody affinity column as well as neutralization with polyclonal PrP 27-30 antibodies.…”
mentioning
confidence: 99%
“…One of the major problems facing investigators studying most neurodegenerative diseases is the lack of animal models that recapitulate all features of these disorders (23). Although Alzheimer's disease is not transmissible (25) and its amyloid does not contain detectable amounts of PrP (36,52), biochemical processes similar to those in prion diseases may be involved. Posttranslational modification of a normal cellular protein to an abnormal polymerizing isoform may be a process common to several degenerative diseases, and initiation of the pathological cascade could be caused by defects in the protein gene itself or in "incubation time" loci, as well as by environmental insults.…”
mentioning
confidence: 99%
“…15,27 Furthermore, histopathological studies of brains of scrapie-infected animals and Creutzfeldt-Jakob disease patients revealed the accumulation of PrP Sc in congophilic amyloid plaques. 28,29 Finally, in vitro, PrP formed rod-like aggregates that exhibited apple-green birefringence upon binding Congo Red. 30 With these characteristics being major hallmarks of amyloids, experimental evidence indicated that PrP was an amyloidogenic protein.…”
Section: Introductionmentioning
confidence: 99%